Their Cup of Tea: Emotions and Drinking in Victorian-Era Literature - Lile Kobaliani,; Raquel Correia de Souza,; Felipe Jacob Ferreira, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Victorian society, characterised by industrial expansion, economic growth, and a strong emphasis on imperialism, was equally renowned for its adherence to tradition and a preserved way of life, in which personal and collective emotions were often kept beneath the surface, rather than openly expressed. However, as art always mirrors the Zeitgeist, Victorian-era literature has not failed to identify such nuances. The goal of this article was to explore the connection, from a digital humanities perspective, between drinking habits and emotional expression in Victorian literature, focusing on alcoholic beverages but also other drinks like tea, coffee, and lemonade. Our study uncovered patterns that reveal how drinking practices shaped personal and social emotions. The corpus of analysis consists of ten major Victorian novels through distant reading methods and sentiment analysis conducted in R. We observed that emotions related to drinking were largely negative, with alcohol playing a significant role in how emotions were portrayed. Interestingly, almost half of the passages reflected negative emotions, challenging the common belief that Victorian literature often leans toward more positive expressions. The findings also suggest that drinking was closely tied to both public and private emotional experiences, mirroring larger societal concerns about morality, social status, and gender in the Victorian era. This research offers a deeper insight into how emotions are represented in Victorian literature and points to the need to explore further the links reflected through art, between emotions, drinking behaviours, and gendered social norms during this period, which can have significant comparative relevance to modern-day.